ANALYSIS OF LEADERSHIP STYLE ON PERFORMANCE (CASE STUDY EMPLOYEE OF DIRECTORATE OF INFRASTRUCTURE INVESTMENT DEVELOPMENT, MINISTRY OF PUBLIC WORKS AND HOUSING) - Jeffy Alfanny (Institut Teknologi Sepuluh Nopember, 2018)
ABSTRACT Leadership is a key element in an organization. The soul of leadership must be owned by every leader who has the main task of managing activities in the organization. This study aims to determine the desired leadership style in the working environment of Directorate of Infrastructure Investment Development (DBII), Ministry of Public Works and Housing. This research uses quantitative approach using survey method, priority-scale approach, regression analysis and focus group discussion (FGD).The results showed that there were at least 3 (three) leadership styles commonly used by leaders namely, authoritarian, delegative and participatory styles. Based on the survey and FGD results, participative leadership style is the preferred style of leadership in the work environment of the Directorate of Infrastructure Investment Development while the regression results show that the leadership style of participatory has a positive influence with performance. Participative leadership style can be implemented in leadership development activities in the working environment of Directorate of Infrastructure Investment Development but still needed coordination and agreement from internal party and related external institution having capacity and competence in human resource development. Keywords: Authoritarian, Delegative, and Participative Leadership Style, Performance.